Eye-hand coordination during upper limb motor tasks in individuals with or without a neurodevelopmental disorder: a systematic review - Abid, Manel; Poitras, Isabelle; Gagnon, Martine; Mercier, Catherine (Frontiers in Neurology, 2025)
BackgroundIndividuals living with neurodevelopmental disorders (NDD) often face challenges in performing daily manual activities that require precise visuomotor coordination. This systematic review aimed to characterize the differences between individuals with and without NDD in spatiotemporal eye-hand coordination when performing upper limb (UL) motor tasks.MethodsThe following databases were systematically searched: CINAHL Plus with Full Texts (EBSCOhost), EMBASE.com, WEB OF SCIENCE core collection, All Ovid MEDLINE(R) and ERGONOMICS ABSTRACTS (EBSCOhost) in December 2022 and re-searched in April 2024. The studies selection was performed independently by two researchers according to the following inclusion criteria: (1) individuals diagnosed with NDD; (2) inclusion of aged-matched control (CTRL) group; and (3) measurement of spatial and/or temporal coupling between oculomotor control and UL motor control during an UL task.ResultsTwelve articles were included with a total of 427 participants. Most of the included studies (75%) were high-quality papers, and the remaining ones were of moderate quality. Participant’s NDDs were mainly developmental coordination disorder, cerebral palsy or autism spectrum disorder. The UL tasks performed in these studies were categorized as pointing tasks, manipulating tasks or tracing and copying tasks. Eye-hand coordination temporal pattern did not differ between individuals with and without NDD in simple tasks involving direct pointing at a single stationary target. In the case of more complex tasks in terms of visuomotor and/or cognitive integration, especially for the more complex manipulation or sequential movements, individuals with NDD exhibited significantly different behaviors, with larger temporal gaps between the timing of eyes movement relative to that of the hand and more reliance on visual monitoring of hand movements.ConclusionThe results of this systematic review suggest that individuals with NDD face significant challenges in efficiently integrating visual and motor information during UL tasks that are visually, cognitively and/or physically more demanding, with more reliance on visual feedback control. These findings emphasize the importance of monitoring eye-hand coordination deficits in this population to further improve and tailor therapeutic interventions.